Development of a highly sensitive colloidal gold semiquantitative method for the determination of difenoconazole residues in citrus - Wang, Ruobing; Gong, Min; Liu, Yang; Zhu, Weiran; Zhang, Kai; Zhao, Yidi; Yin, Chen; Liu, Yuan; Wang, Jian; Wan, Yuping (Frontiers in Nutrition, 2024)
Difenoconazole(DIFE) is a common pesticide used in citrus cultivation, excessive intake can cause neurological damage to the organism, and the existing colloidal gold immunochromatographic test strips cannot meet the requirements for the detection of citrus samples Difenoconazole was prepared based on the colloidal gold immunochromatographic technique (GICT) and its application in citrus samples was investigated; (2) With colloidal gold (CG) as the probe, the optimization of GICT parameters and the determination of reaction method, the immunochromatographic test strips for the detection of DIFE in citrus was developed, and the limit of detection (LOD), specificity, accuracy and stability of the test strips were verified; (3) The results manifested that the visual detection limit of the prepared colloidal gold immunochromatographic test strips was 0.2 mg/kg and the quantitative range was 0.06-0.6 mg/kg, and the test strips could specifically identify DIFE and had no cross reaction with other common triazole pesticides, The detection method established in this study was verified by GC-MS method, and the detection results achieved good consistency (R 2 >0.98); (4) The conclusion is that the test strips developed in this study have good performance and can be used for highly sensitive detection of citrus samples.